Mapping of dental caries incidence based on geographical information system (gis) in elementary school - Supriyana, Supriyana; Sunarjo, Lanny; Prasko, Prasko; Aditya, Moh Imam Santoso Alif Krisna (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Dental caries in Central Java, Indonesia is still important problem, around 43.45% even prevalence of caries in early childhood is still high around 82%. As an effort to control and prevent increasing that case, a risk analysis is needed to determine the risk factors supporting caries. Geographical information system (GIS) as a delivery of information on the spread of disease to support planning efforts. Aim of this study is to determine mapping of distribution dental caries incidence based on GIS concerned to analysis of caries risk factors at Elementary School in Semarang. Methods: Using cross sectional analytic survey with spatial vector map data of 31 public elementary schools at Banyumanik district, Central Java and attribute data on distribution of dental caries. Mapping distribution of caries incidence based on secondary data from City Health Office and Community Health Centre using (Quantum GIS QGIS) and Web GIS software. Results: Elementary schools with caries risk factor environment were good (n=16, 52%) and bad (n=15, 48%), otherwise those with health services were good (n=22, 71%) and bad (n=9, 29%). There was a relationship between caries risk factors and dental caries incidence (p value=0.004) and OR 19.83 (environment) and p value=0.027 and OR 7.917 (health services). Conclusion: Mapping distribution of caries incidence based on GIS was in a very high category influenced by bad environmental factors and poor health services.